Dinamika Psikologis Tokoh Alie Dalam Novel Rumah Untuk Alie Karya Len Liu: Kajian Psikoanalisis Sigmund Freud - Azima Faqiha Supi’in; Hespi Septiana (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This study examines the psychological dynamics of Alie, the protagonist of the novel Rumah untuk Alie by Len Liu, through the lens of Sigmund Freud's psychoanalytic theory. The novel portrays a child who experiences physical and psychological violence within a dysfunctional family after being blamed for her mother's death. This research aims to describe the forms of fear and violence experienced by Alie, to analyze the dynamics of her personality structure (id, ego, and superego), to identify the defense mechanisms she employs, and to explain the relevance of these psychological findings to real-life issues of child abuse and trauma. A qualitative descriptive method was applied through repeated reading and note-taking of narrative excerpts, dialogues, and paragraphs that reflect Alie's psychological condition; the data were coded and analyzed based on Freudian indicators and validated through source and theory triangulation. The results show that Alie experiences physical, psychological, and social fear as well as physical and psychological violence, which generate realistic, neurotic, and moral anxiety. The tension among id, ego, and superego produces an unresolved inner conflict, prompting Alie to rely on defense mechanisms such as repression, regression, rationalization, projection, and withdrawal. These findings confirm that childhood violence leaves lasting psychological wounds that shape personality, behavior, and social relationships, underlining the literary and educational value of the novel in raising awareness of child protection and trauma recovery.